Curriculum Updates and Their Impact on School Management Practices - Latif, Muhammad Sabri; Nuzula, Jannatul Firdausi; Marno, Marno (Muróbbî: Jurnal Ilmu Pendidikan, 2024)
Curriculum renewal influences not only educational content, but also overall school management practices. In this study, we investigate the impact of curriculum reform on school management practices with an interdisciplinary approach. Through a literature review, we identified various forms of impact, including changes in management paradigm, organizational structure, school culture, teacher skills, education quality, community involvement, management skills, resource quality, student involvement, and service quality. Our findings suggest that school management must adapt planning, training, resource provision, and community involvement to manage change. Regular evaluations are needed to develop more effective education policies and school management practices, with policy adjustments based on evaluation findings. Good communication and involvement of all stakeholders is the key to implementing significant changes in increasing educational effectiveness.